2018
DOI: 10.1098/rsta.2017.0171
|View full text |Cite
|
Sign up to set email alerts
|

A ‘shallow bathtub ring’ of local sedimentary iron input maintains the Palmer Deep biological hotspot on the West Antarctic Peninsula shelf

Abstract: Palmer Deep (PD) is one of several regional hotspots of biological productivity along the inner shelf of the West Antarctic Peninsula. The proximity of hotspots to shelf-crossing deep troughs has led to the 'canyon hypothesis', which proposes that circumpolar deep water flowing shoreward along the canyons is upwelled on the inner shelf, carrying nutrients including iron (Fe) to surface waters, maintaining phytoplankton blooms. We present here full-depth profiles of dissolved and particulate Fe and manganese (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
73
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 43 publications
7
73
0
Order By: Relevance
“…Although many stations had dFe concentrations that hovered around the growth‐limiting level of 0.1 nM (Sedwick et al, ), we observed no evidence of dFe stress in phytoplankton (Arrigo et al, ). Early‐season iron sources in the WAP include sedimentary input from both deep wintertime mixing throughout the water column (Annett et al, ) and horizontal transport from coastlines (Sherrell et al, ), upwelling of Circumpolar Deep Water onto the WAP shelf (Dinniman et al, ; Measures et al, ), sea ice melt (Annett et al, ; Wang et al, ), glacial melt (Annett et al, , ), and precipitation (Annett et al, ). As the season progresses, sea ice melt and warming stratify the water column (Smith et al, ), lifting light limitation but making it more difficult to mix dFe into surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…Although many stations had dFe concentrations that hovered around the growth‐limiting level of 0.1 nM (Sedwick et al, ), we observed no evidence of dFe stress in phytoplankton (Arrigo et al, ). Early‐season iron sources in the WAP include sedimentary input from both deep wintertime mixing throughout the water column (Annett et al, ) and horizontal transport from coastlines (Sherrell et al, ), upwelling of Circumpolar Deep Water onto the WAP shelf (Dinniman et al, ; Measures et al, ), sea ice melt (Annett et al, ; Wang et al, ), glacial melt (Annett et al, , ), and precipitation (Annett et al, ). As the season progresses, sea ice melt and warming stratify the water column (Smith et al, ), lifting light limitation but making it more difficult to mix dFe into surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that Stations 10, 11, and 27 fall along the same dilution/mixing gradient for dFe with increasing distance from the shelf as the other PET stations south of the SB. Power relationships between integrated dFe concentrations and distance from the coast have been observed in other sectors of the Southern Ocean where continental margins constitute an important dFe source (e.g., de Jong et al, ; de Jong et al, ), and the contribution of shallow sediments to strong vertical dFe gradients in waters proximate to the Antarctic continent was recently highlighted by Sherrell et al ().…”
Section: Discussionmentioning
confidence: 85%
“…While bringing together this unprecedented dataset, our understanding would be improved even further if it was possible to include data from throughout the year, in addition to summer snapshots. Primary production along the WAP is strongly linked with sea-ice duration, extent and timing of spring melt, and the impact of these factors on water column stability and light availability [3][4][5] and inputs of key macronutrients and trace elements from a variety of sources, linked with glacial meltwater and sediment interactions [6][7][8]. 'Productivity hotspots' of high phytoplankton standing stocks, such as Palmer Deep and Marguerite Bay, provide an example of extreme heterogeneity in WAP primary production.…”
mentioning
confidence: 99%
“…Kohut et al [10] use high-frequency radar to show that the residence time of phytoplankton is much shorter than their growth rate, implying that phytoplankton are concentrated in 'hotspots' by physical transportation rather than by growing in situ, and canyons are 'conveyor belts' rather than 'incubators'. There is increasing evidence that shelf sediments may be a more important source of macronutrients and trace elements than deep water [6,8], in addition to water column modification due to organic matter remineralization [7]. New geochemical analyses from Sherrell et al [8] show that there is a considerable supply of key trace elements, such as iron, by horizontal advection of particulate and dissolved species from shallow sediments (constituting a 'bathtub ring') providing localized rather than regional supplies from water masses [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation